A Spreadsheet Program (ScallopEx) to Calculate Paleovelocities From Cave Wall Scallops - Emily Woodward; Ira D. Sasowsky (Acta Carsologica, 2009)
The determination of paleovelocities through analysis of scallops on cave walls is an important part of paleohydrologic analysis. The linked equations that must be solved to do this are cumbersome, though. This paper presents a spreadsheet program that simplifies the process. The user enters scallop lengths, paleotemperatures, and passage dimensions; and the program returns velocities.